Relationship between mandible morphology and leaf preference in leaf-cutting ants (Hymenoptera: Formicidae) - Camargo, Roberto Da Silva [UNESP]; Hastenreiter, Isabel Neto; Forti, Luiz Carlos [UNESP]; Santos Lopes, Juliane Floriano (Soc Colombiana Entomologia-socolen, 2015)
Morphological differences among mandibles of grass and leaf-cutting ant species were examined. Specifically, we compared morphometric measurements from mandibles of four species (Atta laevigata, A. bisphaerica, Acromyrmex balzani, and Ac. subterraneus). It was found that these Atta species had similar mandible morphologies, primarily differing in distal tooth length. In contrast, the two Acromyrmex exhibited considerable variation in morphology: Ac. balzani mandibles are more robust and massive, while Ac. subterraneus mandibles are elongated. These results support that morphological differences in mandible shape and dentition are related to preference for either grasses or eudicot leaves.
Keywords: Grasses; Eudicots leaves; Morphometry; Ant jaws